Degenerated (Ancient) Schwannomas: Unraveling Unusual Locations and Treatment Management - Ali Dalgıç; Servet Güreşci; Bekir Tunç; Egemen Işıtan; Zeynep Dağlar; Emin Çağıl; Yigit Can Senol; Goksal Gunerhan (Genel Tıp Dergisi)
Background/Aims:Schwannomas, originating from Schwann cells in peripheral nerve sheaths, exhibit diverse clinical manifestations and unpredictable behavior. Among them, ancient schwannomas, with distinctive degenerative features, present in atypical locations and pose diagnostic challenges. This study explores their unique characteristics and implications for diagnosis and management. Material and Methods: The study was designed as a retrospective analysis of 7 adult patients aged ≥18 years, diagnosed with paraspinal, presacral, sacral, or para-aortic tumors, all confirmed histologically as ancient schwannomas. Data for analysis were collected from patients treated and followed up at Ankara City Hospital between April 2017 and December 2022. Ethical approval and informed consent were obtained before inclusion in the study. Results: The most common symptoms included the presence of a local lump (71,4%) and localized or radiating pain (57,1%). Notably, 1 patient (14,2%) was incidentally diagnosed during the evaluation process. Surgical intervention played a crucial role in the management of these tumors, with 71,4% of patients undergoing complete resection, while 28,5% underwent subtotal resection. Tumor recurrence occurred in 42,8% of cases, prompting the administration of radiotherapy as part of the treatment strategy. Imaging findings, particularly on MRI, played a crucial role in the accurate identification of ancient schwannomas. These tumors displayed isointensity on T1-weighted images and heterogeneous hyperintensity on T2-weighted images, along with distinctive heterogeneous contrast enhancement. Conclusion: Ancient schwannomas exhibit unique histological features and distinctive MRI characteristics, differentiating them from other nerve sheath tumors. Early diagnosis and complete surgical resection offer favorable outcomes. Awareness of this entity is essential for managing peripheral nerve sheath tumors effectively.